Antidiabetic and neuroprotective effects of a novel repaglinide analog. Issue 9 (15th June 2022) - Foroumadi, Roham; Baeeri, Maryam; Asgarian, Sara; Emamgholipour, Zahra; Goli, Fereshteh; Firoozpour, Loghman; Keykhaei, Mohammad; Gholami, Mahdi; Dehpour, Ahmad R.; Abdollahi, Mohammad; Foroumadi, Alireza
Abstract: Repaglinide (RPG) is an oral insulin secretagogue used in the treatment of diabetes. In this study, a new RPG analog was synthesized. Its antidiabetic and neuroprotective effects on dorsal root ganglions (DRG) in streptozotocin (STZ)‐induced diabetic rats were examined compared to RPG. To assess the effects of 2‐methoxy‐4‐(2‐((3‐methyl‐1‐(2‐(piperidin‐1‐yl)phenyl)butyl)amino)‐2‐oxoethoxy)benzoic acid (OXR), the impact of OXR on oxidative stress biomarkers, motor function, and the expression of the glutamate dehydrogenase 1 (GLUD1), SLC2A2/glucose transporter 2 (GLUT2), and glucokinase (GCK) genes in STZ‐induced diabetic rats were assessed. DRGs were examined histologically using hemotoxylin and eosin staining. Molecular docking was used to investigate the interactions between OXR and the binding site of RPG, the ATP‐sensitive potassium (KATP) channel. Following 5 weeks of treatment, OXR significantly increased the level of total antioxidant power, decreased reactive oxygen species, and lipid peroxidation in the DRGs of diabetic rats. OXR restored STZ‐induced pathophysiological damages in DRG tissues. Administration of OXR improved motor function of rats with diabetic neuropathy. Administration of 0.5 mg/kg OXR reduced blood glucose while promoting insulin, mainly through upregulation of messenger RNA expression of GLUD1, GLUT2, and GCK in the pancreas. Molecular docking revealed a favorable binding mode of OXR to the KATP channel. In conclusion, OXR has neuroprotective effects in diabetic rats by lowering oxidative stress, lowering blood glucose, and stimulating insulin secretion. We report that 0.5 mg/kg OXR administration was the most effective concentration of the compound in this study. OXR may be a promising target for further research on neuroprotective antidiabetic molecules. Abstract : The effects of a novel repaglinide analog in preventing diabetic neuropathy development.